Pengetahuan Berhubungan dengan Perilaku Personal Hygiene Saat Menstruasi di SMPN 3 Tempel Sleman - Astuti Wulandari Dewi Rahayu; Afi Lutfiyati (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
The need for personal hygiene were important and must be considered. One of the ways to maintain reproductive health in woman were to maintain feminine hygiene. One of the factors that influence personal hygiene were knowledge. Good knowledge would affect health behavior because with ignorance, health behavior weren’t implemented properly, and would cause reproductive tract diseases. The study aimed to identify the association between knowledge about menstruation with personal hygiene behavior during menstruation at SMPN 3 Tempel Sleman. This research type were quantitative with cross sectional approach. The total sampling technique used with 60 female students according to the inclusion and exclusion criteria. Collecting data used questionnaire. Data analysis with Kendall Tau test. The results showed most of the female students’ knowledge about menstruation was in the good category as many as 40 respondents (66.7%), while the personal hygiene behavior during menstruation was mostly in the moderate category as many as 40 respondents (66.7%) with a p-value of 0.036 and ?=0.287. There were an association between knowledge about menstruation with personal hygiene behavior during menstruation at SMPN 3 Tempel Sleman with low association